Analysis of inter-varietal hybridization in rice (Oryza sativa L.) indicate transgressive segregation - Raj, R. Dinesh; Varghese, George; Jose, Mariet; Thomas, George (Current Botany, 2024)
Traits under continuous stabilizing selection may yield transgressive phenotypes in suitable cross combinations. Farmers maintained Njavara (Oryza sativa L. landrace Njavara), a poor yielding medicinal rice landrace in Kerala state over centuries for medicinal applications using short duration (60-70 days) as a selection criterion. This implies that the heading date together with several of the yield related traits, which are co-controlled by pleiotropism, were under constant stabilizing selection in Njavara. We examined the level of transgression in 13 yield related traits in F2 populations raised from crosses between Njavara and a high yielding hybrid variety Jyothi. The cross yielded transgressive phenotype in all of the 13 traits in F2 populations. Difference in the genetic architecture between Njavara and Jyothi due to the difference in the selection pressure experienced by them may have contributed to the excessive transgression observed in the study. The results highlight the value of unattractive poor yielding land races in providing alleles to lift yield barrier in high yielders, and suggest the need to examine the genetic architecture of the trait of interest in parental lines for better genetic advancement in crop improvement programmes.